Complete genome sequence of an extensively drug-resistant Pseudomonas aeruginosa ST773 clinical isolate from North India. (December 2021) - Singh, Sanjay; Pulusu, Chanakya Pachi; Pathak, Ashutosh; Pradeep, Bulagonda Eswarappa; Prasad, Kashi Nath
ABSTRACT: Objectives: Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen causing a wide range of community- and hospital-acquired infections. Here we report the complete genome sequence of an extensively drug-resistant (XDR) P. aeruginosa strain (PA790) in order to understand the antibiotic resistance genes (ARGs) harboured by such a strain. Methods: Whole-genome sequencing (WGS) was performed using Illumina HiSeq and Nanopore MinION platforms. Genome assembly was performed using Unicycler v.0.4.8. The genome was annotated using the NCBI Prokaryotic Genome Annotation Pipeline (PGAP). In silico predictions were fulfilled using curated bioinformatics tools. Results: Pseudomonas aeruginosa PA790 was classified as XDR and belongs to sequence type 773 (ST773). The complete genome size is 6 932 250 bp with a G+C content of 66.02% and a BUSCO (Benchmarking Universal Single-Copy Orthologs) score of 100. Strain PA790 harboured 12 different ARGs conferring resistance to eight different classes of antibiotics. It was identified as the nineteenth ST773 strain among 5785 whole-genome sequences of P. aeruginosa available in the NCBI database. Conclusion: Pseudomonas aeruginosa PA790 belongs to ST773 and was identified as the nineteenth such isolate to be submitted to NCBI and the first complete ST773 genome from India. The WGS data with multiple ARGs of P. aeruginosa PA790 (ST773) will aid in understanding the evolution and phylogeny of such high-risk clones and provide a solid basis for further research on XDR strains.